CdSe-based photodetectors for visible-NIR spectral region - Kumar H.; Jit S. (My University, 2025)
This chapter focuses on the CdSe based photodetectors ranging from visible to near-infrared (NIR) regions. Detailed emphasis is given over the carrier dynamics of the CdSe and its impact over the photodetector properties. Further, different device structures namely photoconductors, Schottky diodes, heterojunction diodes and also recent advances in hybrid photodetector devices containing CdSe as an active material is discussed. Finally, we have also outlined some potential applications of CdSe based photodetectors. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.